Marketing hope : get-rich-quick schemes in Siberia - Schiffauer, Leonie (Berghahn Books, 2019)
Multilevel marketing and pyramid schemes promote the idea that participants can easily become rich. These popular economies turn ordinary people into advocates of their interests and missionaries of the American Dream. Marketing Hope looks at how different types of get-rich-quick schemes manifest themselves in a Siberian town. By focusing on their social dynamics, Leonie Schiffauer provides insights into how capitalist logic is learned and negotiated, and how it affects local realities in a post-Soviet environment.